Genetic Analysis of Fibre and Earliness Parameters in F2 Progenies of Intra-hirsutum Crosses (Biological Sciences - PJSIR, 2008)
Study of ten F     progenies of cotton along with their ten parental lines showed that the mean performance of genotypes differed significantly for the traits fibre length, seed index, lint index, micronaire value and earliness. Among F hybrids, progeny CIM-499 x NB-111/S exhibited maximum heritability percentage for lint index and seed index, whereas progeny VH-142 x CRIS-134 expressed high genetic advances for fibre length and micronaire value. Progeny BH-147 x CIM-511 exhibited fair amount of genetic variance for earliness. The studied breeding material hence may reliably be used as a potential segregating population to improve fibre and earliness attributes in cotton.